Social franchising in healthcare: a systematic review and narrative synthesis of implementation and outcomes - Shams El Arifeen; Ahmed Ehsanur Rahman; Anisuddin Ahmed; Aniqa Tasnim Hossain; Ridwana Maher Manna; Md Hafizur Rahman; Janet E. Perkins; Nasimul Ghani Usmani; Md Refat Uz Zaman Sajib; Ema Akter; Mohammad Sohel Shomik (BMJ Global Health)
Introduction The growing prominence of social franchising in healthcare underscores the need to analyse its implementation and impacts; however, substantial research gaps remain. Therefore, we aimed to conduct a systematic review and narrative synthesis of evidence to analyse the social franchise models, implementation and outcomes.Methods We conducted a systematic literature search in February 2024 on Medline, Embase, PubMed, Web of Science, CINAHL and Scopus using terms related to ‘social franchising’ in healthcare. We conducted a qualitative narrative synthesis of study findings into five thematic areas: client impact and utilisation, healthcare outcomes, financial sustainability, innovative technologies and awareness activities.Results From 4184 search results, 47 studies were included in the analysis. We identified 29 social franchises across 25 countries. Social franchises were mostly present in Africa, Asia and Central America. Most franchises focused on sexual, reproductive and maternal health (n=18) and family planning (FP) (n=25), and most included training (n=21), service provision (n=17) and financial support (n=12). Franchising improved client volumes, satisfaction and contraceptive continuation rates and increased access to healthcare. Vouchers and subsidised services reduced the financial burden among clients. Telemedicine and call centres enhanced healthcare delivery, and community outreach and marketing increased awareness and modern contraceptive use. However, franchises struggled to reach poorer populations due to high fees and competition from public services. It often did not improve FP, reproductive healthcare and child nutrition and had limited branding and promotional activities. Additionally, heavy reliance on donor funding threatened long-term sustainability.Conclusion Social franchising presents a potential strategy for expanding healthcare access and improving service delivery, though outcomes regarding the effectiveness of social franchising vary across regions. More research is needed to evaluate digital technology use and the long-term impact, equity and sustainability of social franchising.PROSPERO registration number CRD42022328104.